A COMPARISON OF SEALING CAPABILITIES OF AMALGUM, GIC AND ZINC OXIDE EUGENOL CEMENT WHEN USED AS RETRO GRADE FILLING MATERIALS (IN VITRO STUDY) - Ansari, Shuja Riaz; Qayyum, Zahur; Khitab, Umar (Journal of Ayub Medical College Abbottabad, 2003)
Background: The objective of this study was to compare sealing capabilities of different filling materials when used as retrograde filling materials following apiceotomy (to check their sealing abilities as retro filling). In this study apical seal obtained following reverse retrograde root filling with amalgam, was compared with those obtained with, Glassinomer (GIC) and Zinc oxide eugonal (ZnO2E) cement. Methods: The root canals of 50 extracted single rooted upper anterior human teeth were used in this study. The root canals were instrumented and obturated with laterally condensed, gutta-percha and zinc oxide sealer. Each tooth was apically resected at 90 degrees to its long axis and the root surface isolated with two coats of nail polish. Teeth were divided into 4 groups, the 1st group received amalgam retrograde filling, the 2nd and 3rd group was retro filled with GIC and ZnO2E cement respectively and the 4th control group received no retrograde root filling. All these teeth were suspended in 1% methylene blue dye at room temperature for 72 hours, the roots were sectioned and dye penetration measured by using (stereomicroscope) microscope. The sealing abilities of these materials were determined by their ability to inhibit dye penetration.Results: The result of this study has shown that GIC is just as effective as amalgam but ZnO2E cement showed poor sealing abilities. Conclusion: GIC is just as effective as Amalgam as a retro-sealer and on some instance, better then it, but a long term in vivo study is required to prove it. Key words: Retrograde filling, Apiceotomy, Endodontic surgery.